Muhamad Abed Al Jabiri and Ideas on Reconstruction of Islamic Thought: A Study of Literature - Subhan, Muhammad (TAJDID, 2020)
This article attempts to dissect the thoughts of Muhammad Abed Al Jabiri and his ideas on the reconstruction of Islamic law. This titration analysis study has succeeded in revealing that the dominance of kalam and Sufism which is too strong has caused Islamic epistemology to not develop naturally. Departing from this, Muhamad Abed Al Jabiri offers an epistemological reconstruction to help develop religious knowledge that is considered different from science in the Western world. In general, Jabiri's criticism is directed at Arab-Islamic reasoning which is ultimately integrated into turats or culture. In Jabiri's view, culture should be the starting point for criticism of reason so that the Arab revival project does not experience a historical break. Because the problem of the downturn of the Arabs actually revolves around the way they understand and treat culture, which tends to move circularly and does not move towards renewal. In this case, the epistemology of Islamic studies offered by Jabiri includes three aspects, bayâni, irfâni and burhâni.